Australian Podiatry Research in Workforce and Education: A Bibliometric Analysis - Ho, Malia; Tehan, Peta; Carroll, Matthew; Williams, Cylie (Wiley, 2026)
Background To conduct a bibliographic analysis of English language research pertaining to podiatry workforce and education by Australian authors. Methods The Scopus database search was conducted to identify all Australian workforce and education-related articles published by podiatric authors in English from 1970 to 2024. Bibliometric analysis was performed using Biblioshiny, a web-based graphical interface for the bibliometric R package. Citations, journals, authors, institutions, and countries were described. Publications were manually categorised according to research type, level of evidence and funding source. Results The search strategy yielded 105 eligible articles, which received a total of 975 citations and were published by 338 authors in 33 journals. The most frequent journal was Journal of Foot and Ankle Research (34 articles; 32%), and the most frequently cited was the University of South Australia (affiliation of 85 authors). Most Australian workforce and education articles published by podiatrists focused on health and social care services research (n = 60; 57%) and only five articles (5%) provided level I evidence. Fifty-six articles (53%) reported no research funding. Research generally fell under four themes. Conclusion Workforce and education research make up a small percentage of podiatry-related research. Most are published in low-impact journals with low citations. The articles are highly collaborative, with multiple authors nationally and internationally. Studies are driven by academics with a vested interest in workforce and education issues, with little or no funding. There is a lack of research in continuing professional development educational activities and workforce in the private sector. Being a small profession, podiatry data may be missed in large allied health workforce studies. Podiatry workforce and education research must be driven by the profession, thereby creating opportunities for sustainable podiatry career growth.
Keywords: 1103 Clinical Sciences; 1104 Complementary and Alternative Medicine; 1106 Human Movement and Sports Sciences; 3202 Clinical sciences; 4201 Allied health and rehabilitation science; 4207 Sports science and exercise; bibliometric analysis; education; foot; podiatry; publications; research; workforce